Potential site of Sungai Rawog conservation area, Sabah, as nature-based tourism destination in selected trails - J.L. Dani; O. Jaunis; W.S. Lim; Russel @ Andy Immit Mojiol; B.S. Fatt (Sabah Forestry Department, 2024)
Natural areas offer diverse resources, including those that support tourism in various regions. A comprehensive understanding of the characteristics and importance of these resources is imperative for decision-makers at different layers in order to formulate a suitable strategy for their implementation by management. Hence, the objective of this study was to conduct a survey and identify potential tourist attractions in selected trails within the Sungai Rawog Conservation Area. A total of 10 trails were chosen, including a main road in compartment 55, to assess the touristic potential product. Observations were made, and coordinates and pictures were taken and recorded. The findings revealed that noteworthy huge trees were found in several trails. It could be a pictorial spot with an extensive landscape forest view. Besides, the Kacip Fatimah plant was only available in Trail 2. The Nepenthes trail had an abundance of Nepenthes sp. within the area. The presence of a river nearby could also be a potential tourist attraction, such as river cruising and bird watching. Additionally, wildlife presence was recorded, including elephant excrement in the open area, sightings of eagles, and the nesting of orangutans on a tall tree branch. Therefore, the findings showed that it is crucial to identify the natural attributes as it shows the great potential as a nature-based tourism destination. Sustainable planning and collaborations between stakeholders are crucial for preserving the natural attributes.